DECREASE FUNCTIONAL MOVEMENT OF THE HAND IN DAILY LIFE IN GALEAZZI FRACTURES: CASE REPORT - Martina, Fita; Susilo, Taufik Eko (Universitas Muhammadiyah Surakarta, 2021)
Introduction : The Galeazzi dislocation fracture is a unique injury that involves a fracture of the radial diaphysis, together with a dislocation of the distal radioulnar joint (DRUJ). Galeazzi fractures have poor stability due to disruption of the DRUJ (distal radial ulnar joint) and disruption of the interosseous membrane (IOM), the triangular fibrocartilage complex (TFCC) which acts as the main stabilizer of the DRUJ and the dorsal and volar radioulnar ligaments. Case Presentation : A 58-year-old patient had a chief complaint of limited movement in dorsi flexion and palmar flexion of the left wrist. Management and Outcome : In this case, significant changes were found in muscle strength, and an increase in wrist ROM, but no change in functional ability was evident. Discussion : Early mobilization has been shown to maintain physiological viscoelasticity and connective tissue homeostasis. Early movement up to 1-3 weeks after injury appears to significantly improve bone healing at the site of long bone fracture. Controlled movement is essential to avoid unwanted changes resulting from immobilization and to maintain normal homeostasis and connective tissue viscoelasticity. Conclusion : The role of physiotherapy can reduce the adverse effects of immobilization and help the patient return to pre-fracture function. Physiotherapy management post Galeazzi fracture for 4 times intervention with evaluation done once a week 2 times to see the development of joint range of motion and functional activity in the left wrist, was not seen significantly.